THE DEVELOPMENT OF INDONESIA LANGUAGE AND IMPROVED SPELLING (EYD) - Afifah Nayla; Rosnida; Osama Bhinneka Pulungan (Rahis Cendekia Indonesia, 2024)
The development of Indonesia and Improved Spelling (EYD) reflects the dynamics of language evolution in the historical, social, and cultural context of Indonesia. Indonesia, as the country’s official language,has undergone significant transformation from the colonial era to the modern era. This process not only includes the influence of Malay as a trade language, but also interactions with various regional languanges and global influences. EYD,as the official imdonesia spelling guidance system,hasundergone several changes over time. This approach was adopted to standardize language use and facilitate effective communication across all levels of society. Changes in EYD reflect efforts to update and perfect the language in accordance with current social developments, technology and communication needs.